AGRO-PHYSIOLOGICAL TRAITS OF THREE MAIZE HYBRIDS AS INFLUENCED BY VARYING PLANT DENSITY - M. Ahmad alias H. A. Bukhsh; R. Ahmad; A. U. Malik; S. Hussain; M. Ishaque (Journal of Animal and Plant Sciences, 2010)
Production potential of maize hybrids is determined through their yield and yield contributing attributes, but sometimes maize hybrids are evaluated on the basis of their agro-physiological traits particularly when they are subjected to different plant density levels. For this purpose, an experiment was conducted on a sandy clay loam soil at Government Agricultural Extension Farm, Model Town – A, Bahawalpur. The experiment was laid out in randomized complete block design with split plot arrangement, randomizing maize hybrids (30 DSS, pioneer 3012 and pioneer 3062) in main plots and plant density levels in subplots with four replications. The data were analyzed by the “Mstat” statistical package. It was observed that Pioneer-30D55 surpassed all other two hybrids (Pioneer-3012 and Pioneer-3062) with respect to all agro-physiological traits i.e leaf area index at 75 DAS, leaf area duration (30-90 DAS), and dry matter accumulation (30-90 DAS) with significant variation between them. All the aforementioned traits increased progressively with periodic time period of 15 days, with increase in plant density from 40816 to 95238 plants ha-1 and reverse was found to be true for net assimilation rate. Interactive effects of maize hybrids and plant density levels on all the traits under study were found to be non significant. It is suggested that among these three hybrids Pioneer-30D55 should be preferably cultivated at plant density level 98235 plants ha-1.
Keywords: Maize hybrids; plant density levels; agro-physiological traits